Taxonomic history of the iguanian lizard Liolaemus Pictus major Boulenger, with a revalidation of Liolaemus capillitas Hulse - Espinoza, Robert E. (2011)
Núñez (2004) examined the syntypes of Liolaemus pictus major Boulenger in the British Museum of Natural History and concluded, without supporting data, that this taxon is a senior synonym of Liolaemus capillitas Hulse. We show that the evidence does not support Núñez’s (2004) proposal. We first document the complex taxonomic history of L. p. major, the lack of a precise or even definitive type locality, and the implications of the latter on subsequent checklists and research. Second, we note differences between Boulenger’s (1885) type description of L. p. major and Hulse’s (1979) type description of L. capillitas. Third, we show that the syntypes of L. p. major photographed by Núñez (2004) do not exhibit the character states of L. capillitas. We conclude that L. capillitas is not a synonym of L. p. major. Based on the available evidence, the syntypes of L. p. major are probably assignable to Liolaemus elongatus from populations occurring in Patagonia (southern Argentina or adjacent Chile). However, the precise identity of the syntypes requires additional study and perhaps a type locality restriction or redefinition of L. elongatus, which is itself in a state of flux.